A just culture : restoring justice towards a culture of human rights - McConnell, Jesse (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2005)
This thesis seeks to investigate the possibility that the binary opposition between retributive and restorative forms of justice that structures the discourse on justice is unhelpful and unnecessary, particularly for societies seeking to extricate themselves from violent conflict and towards building peace and democracy. I shall argue for the importance of considering restorative justice as conceptually and historically prior to the possibility of retributive justice rather than the negation of one or the other, as well as advocate the potentially greater transformative power of the values of restorative justice which may provide a constructive alternative to retributive justice in the context of post-conflict peacebuilding.
Keywords: South Africa. Truth and Reconciliation Commission; Reconciliation; Restorative justice; Justice; Human rights; South Africa -- Politics and government -- 20th century